Effect of Body Mass on Oxygenation and Intra-Abdominal Pressure When Using a Jackson Surgical Table in the Prone Position During Lumbar Surgery. Issue 14 (15th July 2018) - Ni, Liya; Fan, Yuhua; Bian, Jinjun; Deng, Xiaoming; Ma, Yu
Abstract : Study Design: Prospective observational study. Objective: To test the hypothesis that different types of surgical frame and the patient's body mass index (BMI) can affect pulmonary compliance, intra-abdominal pressure (IAP), and oxygenation. Summary of Background Data: The oxygenation index (PaO2 /FiO2 ) and IAP are known to be associated with BMI when patients are in the supine position. However, there are few reports on the correlation between BMI, the oxygenation index, and IAP in the prone position, especially when a Jackson surgical table is used. Methods: Thirty-seven adult patients were divided into two groups according to BMI: normal-weight patients (n = 19, BMI: 18.5–24.9 kg m −2 ) and overweight patients (n = 18, BMI ≥ 25 kg m −2 ). After the induction of general anesthesia, patients were turned to the prone position onto either a Jackson surgical table (Mizuho OSI) or a general surgical table (MAQUET; foam pad, China). The patient's IAP, peak airway pressure, pulmonary dynamic compliance (Cdyn ), and oxygenation index were recorded. Results: In overweight patients, there was a greater increase in peak airway pressure and a greater decrease in Cdyn observed when a general surgical table was used compared with the Jackson surgical table. When the Jackson surgical table was used, there was a greater increase in the oxygenation index and a greater decrease in IAP. There was a significant negative correlation between the oxygenation index and BMI and a significant positive correlation between IAP and BMI in the prone position. Conclusion: Turning patients from the supine to the prone position during anesthesia results in an increase in the oxygenation index and a decrease in IAP. Both of these factors are dependent upon the type of surgical frame used and the patient's BMI. The reduction in IAP was particularly significant when a Jackson surgical table was used for overweight patients. Level of Evidence: 4